On the design of CRISPR-based single cell molecular screens - Hill, Andrew J. (Nat Methods, 2018)
Several groups recently coupled CRISPR perturbations and single-cell RNA-seq (scRNA-seq) for pooled genetic screens. We demonstrate that vector designs of these studies are susceptible to ~50% swapping of guide RNA-barcode associations due to lentiviral template switching. We optimize a published alternative, CROP-seq, in which the guide RNA also serves as the barcode, confirming this strategy performs robustly and doubling the rate at which guides are assigned to cells to 94%.